Pengaruh Terapi Bacaan Al-Qur’an (TBQ) sebagai Biblioterapi Islami pada Kesehatan Mental Narapidana Lesbian - Inggriane Puspita Dewi; Redita Aida Suryadi; Siti Ulfah Rifa’atul Fitri (Universitas Faletehan, 2020)
The capacity of detention and prisons in Jawa Barat currently has an excess of up to 52%, one of the impacts that occur is sexual behavior distortion. Deviations in sexual behavior can be caused by low mental of inmates. The use of Islamic bibliotherapy as an intervention for mental health has not been done in this lesbian group. The purpose of this study to find out the effect of Islamic bibliotherapy on mental health of female prisoners who experience sexual orientation deviations (lesbian). Quantitative research with quasi-time series design experiments. The sample of this study was 22 respondents. Respondents were given a Mental Health Inventory, then were given interventions: 1) Al-Quran reading session and 2) reading Islamic bibliotherapy one time every Friday for three consecutive weeks with different themes. The bivariate analysis in mental health used the Repeated Measures Anova. There is an effect of Islamic bibliotherapy therapy mental health (p = 0.001). Islamic bibliotherapy can be an option for spiritual intervention for a group of lesbians to improve their mental health.